The Impact of ICT Usage on Classroom Teaching of Geography in Secondary Schools in Anaocha Local Government Area Anambra State, Nigeria - Iguocha, Christian Arinze; Ifeanyi E, Agulue (Indonesian Journal Education, 2024)
The study was carried out to find out the Impact of ICT usage in teaching geography in secondary schools in Anaocha Local Government Area in Anambra suite. In an attempt to carry out the study, five (5) research questions were formulated to guide the study. Literature reviews were carried out under conceptual framework, theoretical framework, theoretical studies, empirical studies and summary of literature review. The study was a descriptive survey design with the target population of all public secondary schools in Anaocha L. G. A., Anambra State. The collected data were analyzed using means and presented in tables; the results indicated that students were not properly exposed to the level the subject required; lack of skilled teachers; inadequate power supply; etc. Based on the findings, recommendations were made; the government should be made to put in place a regular power supply as well as reducing the cost of computer facilities to affordable price. In addition, lecturers should be sensitized on the various ways and process of using ICT materials in teaching and learning of geography through workshops, seminars, and conferences.